Polarisome scaffolder Spa2-mediated macromolecular condensation of Aip5 for actin polymerization - Ying Xie (Nature Portfolio, 2019)
The polarisome is a dynamic protein complex that nucleates F-actin for polarized yeast growth, but its regulation is unclear. Here, the authors report that the polarisome protein Aip5 undergoes Spa2-mediated phase separation in physiological and stress conditions, potentially for regulating actin assembly.